Psychometric evaluation of the Hospitalisation‐Related Stressors Questionnaire for Elderly Patients. Issue 2 (22nd December 2020) - Yildirim, Hilal; Işik, Kevser
Abstract: Background: Stress can threaten the health and recovery of patients, and determining the level of stress can be an important factor in curing illnesses. The aim was to adapt the Hospitalisation‐Related Stressors Questionnaire for Elderly Patients (HRSQ‐EP) and perform its psychometric evaluation. Methods: In the study, the method of developing a scale and determining the construct validity and reliability of this scale was used. The research was carried out with elderly patients who were hospitalised. The research was conducted in two main phases; in the first phase, after providing expert opinion for the language validity of the scale, the content and face validity were confirmed and then confirmatory and exploratory factor analyses were applied for content validity and reliability in the second phase. Results: The new scale, which was formed as a result of evaluating the construct validity, consisted of three factors and 15 items, and all factors explained 67.1% of the total variance. Kaiser‐Meyer‐Olkin, which determined the suitability of the measurement tool for factor analysis, was determined as 0.901 and Bartlett test 0.000. The adapted short form is a simple and easy‐to‐understand tool for determining the stress levels of hospitalised elderly individuals. HRSQ‐EP provided evidence that it demonstrates adequate internal consistency, reliability and construct validity. Conclusion: The results suggested that the adapted measurement tool will be useful. The scale is recommended to be evaluated in different populations to determine cultural differences.